มาตรการการปรับปรุงประสิทธิภาพพลังงานในกระบวนการผลิตสำหรับอุตสาหกรรมเซรามิก - ฐาปนพงษ์ ลาธุลี (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The main purpose of this thesis is to find the measures in improving the energy’s efficiency for the ceramic industry. The example factory 1 using base load compressed air can reduce electrical energy consumption 10,307.40kWh/year. The example factory 2 using minimizing leakage in compressed air that can be saved 19,877.8 kWh/year. The example factory 3 improves efficiency in kiln by combustion control that can be saved energy consumption 122,752.69 kg/year. The example factory 4 uses waste heat recovery from preheat zone can be saved 283,119.22 kJ/hr and cooling zone can be saved 204,311.23 kJ/hr. The example factory 5 uses waste heat recovery from preheat zone can be saved 1,095,434.41 kJ/hr and cooling zone can be saved 372,640.60 kJ/hr. The example factory 6 using base load compressed air can reduce electrical energy consumption 71,355 kWh/year. The example factory 8 using variable speed drive (VSD) can reduce electrical energy consumption in motor that can be saved 278,260 baht/year. The example factory 9 minimizing leakage in compressed air that can be saved 2,304 kWh/year. The example factory 10 uses waste heat recovery from preheat zone can be saved 536,466 kJ/hr and cooling zone can be saved 326,524.80 kJ/hr. The example factory 12 uses waste heat recovery from preheat zone can be saved 408,772.44 kJ/hr and cooling zone can be saved 159,872.76 kJ/hr. The example factory 13 uses waste heat recovery from preheat zone can be saved 285,240 kJ/hr and cooling zone can be saved 159,872.76 kJ/hr. The example factory 14 uses waste heat recovery from preheat zone can be saved 608,164.20 kJ/hr and cooling zone can be saved 316,845.67 kJ/hr.